Cation ratio fluctuations in Cu2ZnSnS4 at the 20 nm length scale investigated by analytical electron microscopy. Issue 9 (5th April 2016) - Aguiar, Jeffery A.; Erkan, Mehmet E.; Pruzan, Dennis S.; Nagaoka, Akira; Yoshino, Kenji; Moutinho, Helio; Al‐Jassim, Mowafak; Scarpulla, Michael A.
Abstract : Kesterite Cu2 ZnSn(S, Se)4 (CZTSSe) is a sustainable material for thin‐film photovoltaics with device efficiencies greater than 12% have been demonstrated. Despite similar crystal structure and polycrystalline film microstructures, there is widespread evidence for larger‐amplitude potential and bandgap fluctuations in CZTS than in the analogous Cu(In, Ga)Se2 (CIGSe) chalcopyrite material. This disorder is believed to account for a sizable part of the larger open‐circuit voltage ( V OC ) deficit in CZTS devices, yet the detailed origins and length scales of these fluctuations have not been fully elucidated. Herein, we present a transmission electron microscopy study focusing on composition variation within bulk multicrystals of CZTS grown by the travelling heater method (THM). In these slow‐cooled, solution grown crystals we find direct evidence for spatial composition fluctuations of amplitude <1 at.% (∼5 × 10 20 cm −3 ) and thus, explainable by point defects. However, rather than being homogeneously‐distributed we find a characteristic 20 nm length scale for these fluctuations, which sets a definite length scale for band gap and potential fluctuations. At Σ3 grain boundaries, we find no evidence of composition variation compared to the bulk. The finding highlights such variations reported at grain boundaries in polycrystalline thin‐films are direct consequences of processing methods and not intrinsic properties of CZTS itself.